Let b be (1 + 0)/((-5)/(-20)). Suppose -3*q - 6 = -b*q. Suppose -k - 2*k = -q. Solve 0 = -5*s - 3 - k for s.

-1

Suppose 0 = -2*u + u + y, -5*y = -10. Solve q - 6 = -u*q for q.

2

Let r(v) = 3*v + 7. Let z be r(6). Solve -z = -2*x - 3*x for x.

5

Let h = 231 + -224. Solve -9*a + h*a + 6 = 0 for a.

3

Let x = 82 + -79. Solve -2 = -5*r + x*r for r.

1

Let a be 103 - (-1)/(-3). Let h = a - 0. Suppose h*q = -m + 8, -2*q = m - 7 + 1. Solve 0 = 5*n + 7 - m for n.

-1

Suppose 3*n + 13 = 5*v, -2*n - 5 = 3*n. Solve v*f = -2 - 6 for f.

-4

Let m(b) = b3 + b2 - b - 3. Let u be m(2). Solve -3*z = -u*z for z.

0

Let a be 71 + (-6)/2. Let i be -1 + 1 + 4 + -2. Suppose -2*n + 8 = i*n. Solve a - n = d for d.

2

Suppose 0 = 2*f - 4*f + 4. Let k be f + (1 - -3) + -2. Solve k = 4*x + 24 for x.

-5